THE MANUSCRIPT HAS BEEN RETRACTED FROM PUBLICATION DUE TO PLAGIARISM (FORGERY OF IMAGES). - Article Retracted, (International Journal of Applied Pharmaceutics, 2020)
The manuscript has been retracted from publication due to plagiarism (forgery of images).